Respon Peserta Didik Terhadap Penggunaan Platform Quipper School dalam Pembelajaran Bahasa Inggris - Musmuliadi Musmuliadi (Jurnal Ilmiah Wahana Pendidikan, 2020)
The aim of this study is to know the students’ response toward english learning by using Quipper School platform. This study is survey research. The population of this study are the eleventh grade students IPS at SMAN 3 Selong. The sample of this study is eleventh grade students IPS 2. The data is collected by using quisioner contain of statements should be answered by the responden. Types of data are response scores of students response then anlaysed by quisioner score obtain criteria persentation. The criteria interpreted in some categories such as very good, good, good enough, and not good category. The result of data analisis of students’ response toward the use of quipper school platform to aspect of use are 89% very good criteria, aspect of the display are 87% very good criteria, and persentation material aspect are 90% very good criteria.